Pendekatan TAM dalam Menilai Keputusan Penggunaan LinkAja Syariah pada Masyarakat Surakarta - Fuad Hasyim; Rya Addela; Novia Gita Rahmawati (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
In this digital era, people are required to transform using e-payments. However, not all levels of society have adapted to digitalization of payments. This study aims to analyze the effect of ease of use, usefulness, and religiosity on the decision to use LinkAja Syariah. This research is a primary quantitative research. The sampling technique was carried out using purposive sampling with convenience sampling. Respondents were obtained by 123 users of the LinkAja Syariah application in the Surakarta area. Data analysis technique using multiple linear regression analysis. The results show that all construct variables consisting of convenience, usefulness and religiosity influence the decision to use LinkAja Syariah in the people of Surakarta.